Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/php.12547
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Cyanine, Merocyanine and Styryl Dye Motifs with Synthetic Bacteriochlorins

Abstract: Understanding the effects of substituents on spectral properties is essential for the rational design of tailored bacteriochlorins for light-harvesting and other applications. Toward this goal, three new bacteriochlorins containing previously unexplored conjugating substituents have been prepared and characterized. The conjugating substituents include two positively charged species, 2-(N-ethyl 2-quinolinium)vinyl- (B-1) and 2-(N-ethyl 4-pyridinium)vinyl- (B-2), and a neutral group, acroleinyl- (B-3); the charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…A small Stokes shift for BCS indicated that the spectroscopic energies are similar to the relaxed energies of the lowest singlet excited state S 1 . This is in accordance with the planar and rigid structure of the tetrapyrolic macrocycle . Therefore, only a minor geometric relaxation takes place in the first excited state.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…A small Stokes shift for BCS indicated that the spectroscopic energies are similar to the relaxed energies of the lowest singlet excited state S 1 . This is in accordance with the planar and rigid structure of the tetrapyrolic macrocycle . Therefore, only a minor geometric relaxation takes place in the first excited state.…”
Section: Resultssupporting
confidence: 83%
“…Each bacteriochlorin in the set contains a common scaffold and was derived by Suzuki coupling with BC‐Br 3,13 . In 2016, Yang et al synthesized two bacteriochlorins ( BC‐3 and BC‐4 ) bearing cationic groups at the 3‐ and 13‐positions of the macrocycle. The substituents of BC‐3 and BC‐4 have characteristics in common with cyanine dyes, which have terminal N ‐alkylated heterocycles at the ends of a polyene chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two others (BC-MEs and BC-EEs) have alkyl (methyl or ethyl) groups at the 2,12-positions and carboethoxy groups attached directly to the 3,13-positions of the macrocycle. 44,45 The absorption spectrum of each bacteriochlorin consists of four major bands: B y , B x in the near ultraviolet, Q x in the greenyellow and Q y in the NIR region. (A) Absorption and fluorescence spectra.…”
Section: (Ii) Photophysical Characterizationmentioning
confidence: 99%
“…Enlarging the π-conjugated system in tetrapyrrolic macrocycles leads to significant alteration of their electronic, optical, and electrochemical properties. Expansion of the conjugated systems can be achieved in several ways, which include attachment of conjugated substituents on the periphery of the macrocycle or assembling the macrocycle into strongly conjugated arrays, i.e., arrays where the linker allows for significant electronic communication between macrocycles. ,, Both approaches lead to derivatives with interesting properties, such as panchromatic absorbance, , high quantum yield of near-IR fluorescence, improved two-photon cross-section, high excited state absorptivity, and large hyperpolarizability . Accordingly, resulting derivatives found applications, for example, as near-IR fluorophores, fluorescent probes, , two-photon excitable singlet oxygen photosensitizers, , models for natural light-harvesting antenna, and photosensitizers for dye-sensitized solar cells. , The extent to which extended conjugation affects the properties of tetrapyrrolic macrocycles depends on the strength of electronic interaction between substituents and macrocycles or between individual macrocycles in dyads.…”
Section: Introductionmentioning
confidence: 99%